Modelo de manutenção integrada para equipamentos de sistemas elétricos e ferramentas computacionais de suporte - Dilmar Goncalves da Cunha (2007)
This dissertation presents the proposal of a maintenance model, supported for specialized computational tools, aiming to supply the necessities and lacks of the maintenance areas of these companies, in a integrated and transcendent way, in order to minimize the risks of blackouts, the loss of upper management support, and consequently to contribute for a sustainable development of the electric sector. The specialized computational tools in equipment maintenance of electrical systems that support the considered model are composed by three independent softwares, but that can change information between themselves, as it follows: Web application: due to its power of make available information on intranets, extranets or even all over the Internet, breaking any geographic barriers, it has the objective to establish a standard in the maintenance methods and also to load a systemic maintenance database. This application opens new perspectives to a global solution for the common problems of the maintenance areas. Desktop application: it aims to allow the use of the mobile computation, the data collectors and the accomplishment of the automated maintenance in real time, which today is so common in the area of the protection equipment. The project philosophy of this application is based on the maintenance expert system, called RME-Win, used by CEMIG since 2001, a practical case of proven success. Standardization Framework: due to its capacity to simplify the programming process, releasing the specialists, normally not programmers, from the heavy load of the programming of the test algorithms, allowing them to focus only in the rules of the maintenance business, it establishes a unique format for the information codification, thus making possible the acquisition of knowledge in a standardized and distributed way and allowing the interchange of information between maintenance areas. In the conclusion of the work the benefits gotten for the maintenance areas are presented, as reduction of costs, quality gains, guarantee of the technological domain, etc. Moreover, it offers new perspectives for the sharing, the interchange, and even the commercialization of standardized methods of maintenance, providing a cooperative and systemic alternative to supply, in an efficient way, the basic and devoid necessities in the majority of the maintenance areas.